Plasma Vitamin D Binding Protein and Risk of Heart Failure in Male Physicians - Petrone, Andrew B. (2013)
Previous studies suggest that vitamin D deficiency may contribute to the pathogenesis of heart failure (HF); however, limited data are available on the association of vitamin D binding protein (VDBP) – a major transport protein for vitamin D – with the development of HF. Thus, we investigated whether plasma VDBP is inversely associated with HF risk. Using a prospective nested case-control design, we selected 464 cases and 464 matched controls from the Physicians’ Health Study for current analyses. VDBP was determined using an enzyme-linked immunoassay. Self-reported HF was obtained through annual follow-up questionnaires and validated in a subsample via review of medical records. We used conditional logistic regressions to compute adjusted odds ratios. The mean age was 58.6 years and the median VDBP was 307.8 (IQR: 265.2–354.6) μg/mL. Plasma VDBP was not associated with HF in our study: OR (95% CI): 1.0 (ref), 1.05 (0.66–1.65), 1.28 (0.80–2.06), 1.07 (0.65–1.75), and 1.28 (0.76–2.15) across consecutive quintiles of VDBP, p for linear trend 0.41, after adjustment for matching factors, body mass index, diabetes, atrial fibrillation, hypertension, and high sensitivity C-reactive protein. In conclusion, our data showed no significant association between plasma levels of VDBP and HF risk in apparently healthy male physicians.